The international calibration procedure for B3 film dosimetry system to ensure the quality irradiated products by 10 MeV electron beam accelerators at VINAGAMMA - Pham Thi , Thu Hong; Nguyen, Thi Ly; Nguyen, Thanh Duoc; Doan , Binh; Cao, Van Chung; Doan, Thi The (Nuclear Science and Technology, 2017)
We performed an in-plant calibration of dosimetry system by electron beam (EB) irradiating the B3 film dosimeters at VINAGAMMA, and inter-compared with the alanine dosimetry, which were supplied and analyzed by Risø High Dose Reference Laboratory (HDRL) as the reference standard. The results revealed that the relative deviation between the values of absorbed doses obtained with our dosimeter and the transfer standards dosimeter measured by HDRL was within the acceptable limitation (about ± 3.0 % in the target range of 2.0-10.0 kGy). And post-irradiation stability of B3 film dosimeters was still maintained after 180 days storage. It is suggested that the B3 film dosimetry could be used in routine radiation processing at VINAGAMMA with the investigated dose range for quality assurance of the irradiated products, specially are foods and foodstuffs processed under the 10 MeV EB accelerator at VINAGAMMA.